Socio-economic implications of the Coronavirus pandemic in Latvia - Steinbuka, Inna; Baranovs, Olegs; Malnacs, Normunds; Austers, Aldis (University of Latvia, 2021)
The spread of COVID-19 requires immediate policy response and future-oriented actions to reduce devastating economic and social impact of crisis and preserve sustainable growth. The aim of this paper is to assess the current economic and social consequenses of the ongoing crisis in Latvia, the government response, public perceptions and future scenarios. Research is based on the macroeconomic assessment and surveybased analysis of people’s attitude towards the government's emergency programs. The comparison of statistically justified findings with the public perception helps formulate conclusions on the future sustainability scenarios and policies.
Keywords: coronavirus crisis; economic resilience; recovery; public perceptions; Research Subject Categories::SOCIAL SCIENCES